Biopsychosocial determinants of cognitive impairment in a representative sample of English older population: Biomarkers (non‐neuroimaging) / Multi‐modal comparisons. (7th December 2020) - Cadar, Dorina; Abell, Jessica; Steptoe, Andrew
Abstract: Background: To investigate various biopsychosocial determinants of cognitive health in later life, using the neuropsychological battery of tests administered in the Harmonised Cognitive Assessment Protocol Sub‐Study of the English Longitudinal Study of Ageing (ELSA‐HCAP). Method: ELSA‐HCAP is a neuropsychological sub‐study of 1273 participants completed in 2018, as part of an international research collaboration designed to better measure and identify neurocognitive disorders in representative population‐based samples. ELSA‐HCAP was administered to participants across all range of cognitive abilities, but we oversampled those identified as having low cognitive scores in the most recent ELSA waves. The HCAP respondent interview covered a broad range of cognitive domains (memory, language, executive function, psychomotor speed, problem‐solving, and numeracy) known to be affected by the ageing process. We also linked ELSA‐HCAP with the previous measures collected across ELSA waves, including biomarkers, psychosomatic and social economic information of these individuals collected in ELSA main waves 4 years before in 2016. We used Structural Equation Modelling (SEM) to estimate direct and indirect associations between Apolipoprotein (APOE) e4 status, education, wealth, inflammatory markers, chronic conditions, quality of life, depression and overall cognitive performance based on multiple domains, as well as the potential mediating effects. Result: Higher levels of education and increased quality of life were protective of the overall cognition, independent of the level of wealth. Depression and chronic conditions were strong predictor of cognitive impairment. We also found significant effects of age and sex, with women showing a slight cognitive advantage compared to men. We did not found an effect of APOE4 allele on cognitive impairment in this study. We find a pathway between higher levels of education leading to higher wealth, which impacting the number of chronic conditions and indirectly impacting on the overall cognition. We also found an indirect effect of inflammatory markers via chronic conditions and depressive symptoms. Conclusion: In a subset sample of a nationally representative sample of English population, we found that specific psychosocial risk factors were associated with the overall cognition in later life. Biological inflammatory markers were indirectly associated with overall cognition via depressive symptoms and chronic conditions pathways.